Thermo-hydraulic performance improvement, heat transfer, and pressure loss in a channel with sinusoidal-wavy surface - Amnart Boonloi; Withada Jedsadaratanachai (My University, 2019)
Thermal efficiency development in a square channel heat exchanger attached with sinusoidal wavy surface is presented numerically. The affectation of flow attack angles ( α = 30°, 45°, and 60°), flow directions or sinusoidal wavy surface arrangements (V-apex directing downstream named “V-Downstream” and V-apex indicating upstream named “V-Upstream”), and amplitude ratios (blockage ratios = 0.10, 0.15, 0.20, and 0.25) for heat transfer and flow structure are examined for laminar flow regime ( Re = 100–1000). The physical model for the present investigation is validated with the correlation data. The current problem is resolved with the finite volume approach (semi-implicit method for pressure-linked equations algorithm). The computational information is illustrated in forms of flow topology and heat transfer mechanism in the square channel heat exchanger. The understanding of flow topology and heat transfer mechanism in the square channel heat exchanger is important knowledge to develop the heat transfer coefficient in the heat exchanger. The present of the sinusoidal wavy surface in the square channel heat exchanger can expand the heat transfer coefficient greater than the plain channel in all examples ( Nu/ Nu 0 > 1). The maximal heat transfer rate is around 5.58 times above the plain square unit with the optimal performance around 1.98.
Keywords: Heat transfer enhancement; Heat Transfer Mechanisms